#ArtVoluntaryWork: Aesthetic experiences in asylum reception centers. - Arnesen, Jon; Gjærum, Rikke Gürgens (Nordic Journal of Art & Research, 2017)
The article discusses the practice of professionals in art didactics doing voluntary work with asylum center residents. The researchers describe and interpret the informants’ execution of phronesis, understood as a form of practical and ethical wisdom. Furthermore, they discuss how this practice, in the context of art didactics, can contribute to the development of cultural democracy. Based on in-depth interviews of seven carefully selected informants, the data is interpreted within a phenomenological research design. The data is discussed in light of Aristotle’s concept of phronesis, and Rancière’s theory of aesthetics in politics and his understanding of the “distribution of the sensible”.